2018
DOI: 10.3758/s13415-018-00670-3
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disadvantage, brain morphometry, and attentional bias to threat in middle childhood

Abstract: Socioeconomic disadvantage is associated with higher rates of psychopathology as well as hippocampus, amygdala and prefrontal cortex structure. However, little is known about how variations in brain morphometry are associated with socio-emotional risks for mood disorders in children growing up in families experiencing low income. In the current study, using structural magnetic resonance imaging, we examined the relationship between socioeconomic disadvantage and gray matter volume in the hippocampus, amygdala,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 147 publications
2
17
1
Order By: Relevance
“…For example, through its associations with prenatal factors, parent-child interactions, and cognitive stimulation in the home environment, socioeconomic status (SES) appears to have a particular influence on the frontal systems in the LH, including the left inferior frontal gyrus [104,105]. Other studies have focused on the lateralized subcortical systems responsible for survival functions involved in learning, emotions, and memories, such as the hippocampus and amygdala [62,[106][107][108][109]. Limbic system structures are believed to be more closely connected with the RH cortex [21,92], leading to the suggestion that attachment experiences preferentially affect right brain networks that are critical to regulatory processes and to the ability to adapt to social-emotional environments [23,92,110].…”
Section: Environmental Effects On Early and Ongoing Development Of Lateralized Neural Functions Associated With Antisocial Behaviormentioning
confidence: 99%
“…For example, through its associations with prenatal factors, parent-child interactions, and cognitive stimulation in the home environment, socioeconomic status (SES) appears to have a particular influence on the frontal systems in the LH, including the left inferior frontal gyrus [104,105]. Other studies have focused on the lateralized subcortical systems responsible for survival functions involved in learning, emotions, and memories, such as the hippocampus and amygdala [62,[106][107][108][109]. Limbic system structures are believed to be more closely connected with the RH cortex [21,92], leading to the suggestion that attachment experiences preferentially affect right brain networks that are critical to regulatory processes and to the ability to adapt to social-emotional environments [23,92,110].…”
Section: Environmental Effects On Early and Ongoing Development Of Lateralized Neural Functions Associated With Antisocial Behaviormentioning
confidence: 99%
“…It does not measure the social class directly, neither the economic status. Although some studies have found brain regions, such as the hippocampus, that appear to be correlated with socioeconomic status (ses), income, and/or stress related to ses (Hanson et al, 2011;Hair et al, 2015;Hanson et al, 2015;Jednoróg et al, 2012;Luby et al, 2013;Yu et al, 2018;Dufford et al, 2018;McDermott et al, 2019), none of them investigated the relation between the brain morphology and only the social status. Even though the score of social status provided by bsmss and the socioeconomic status are related, they are not equivalent (Barratt, 2006).…”
Section: Real Datamentioning
confidence: 99%
“…Childhood socioeconomic status (SES) has been associated with variations in brain structure in children and adults (Dufford et al., 2020; Hanson et al., 2011; Johnson et al., 2016; Noble et al., 2015; Staff et al., 2011). Studies have primarily focused on the associations between family income and gray matter volume in several brain regions including the hippocampus (Dufford et al., 2018; Hanson et al., 2011; Noble et al., 2015), amygdala (Dufford et al., 2019; Hanson et al., 2015; Luby et al., 2013), and prefrontal cortex (Hanson et al., 2013; Lawson et al., 2013). Variations in brain structure associated with childhood SES have been further related to individual differences in cognitive, affective, and socioemotional outcomes in adulthood (Dufford et al., 2018; Johnson et al., 2016; Noble et al., 2015; Palacios‐Barrios & Hanson, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have primarily focused on the associations between family income and gray matter volume in several brain regions including the hippocampus (Dufford et al., 2018; Hanson et al., 2011; Noble et al., 2015), amygdala (Dufford et al., 2019; Hanson et al., 2015; Luby et al., 2013), and prefrontal cortex (Hanson et al., 2013; Lawson et al., 2013). Variations in brain structure associated with childhood SES have been further related to individual differences in cognitive, affective, and socioemotional outcomes in adulthood (Dufford et al., 2018; Johnson et al., 2016; Noble et al., 2015; Palacios‐Barrios & Hanson, 2019). However, these studies are typically cross‐sectional; therefore, with little information on whether childhood SES is prospectively associated with adult brain structure.…”
Section: Introductionmentioning
confidence: 99%